Effect of Photodynamic Therapy on Halitosis: A Systematic Review of Randomized Controlled Trials - Pamella de Barros Motta; Lara Jansiski Motta; Thalita Molinos Campos; Marcela Leticia Leal Gonçalves; Elaine Marcílio Santos; Ana Luiza Cabrera Martimbianco; David José Casimiro de Andrade; Raquel Agnelli Mesquita-Ferrari; Kristianne Porta Santos Fernandes; Anna Carolina Ratto Tempestini Horliana; Sandra Kalil Bussadori (Sensors, 2022)
Background: This systematic review aimed to assess the effectiveness and safety of aPDT for the treatment of halitosis. Methods: Search strategies were conducted in October 2021 without language or data restrictions, on the following databases: MEDLINE, EMBASE, CENTRAL, LILACS and BBO, as well as a manual search. Randomized clinical trials (RCTs) with parallel design were considered for inclusion, assessing individuals (adolescents and adults) with a clinical diagnosis of halitosis treated with photodynamic therapy (aPDT). Primary outcomes assessed were halitosis measurements, adverse events and quality of life. The risk of bias for each included study was evaluated with the Cochrane Risk of Bias tool and the certainty of the body of the evidence was assessed with the GRADe approach. Results: Six RCTs (total of 225 participants) were included and due to clinical diversities it was not possible to group the outcome data in meta-analyses. Based on very low-certainty evidence (GRADE) the results showed that, when compared to tongue scraper, aPDT seems to promote a little to no difference in reducing halitosis and in the microbiological analysis. No adverse events were reported. Considering aPDT combined with tongue scraper, better outcome results were observed when compared to tongue scraper alone. Conclusions: Based on very low-certainty evidence, the findings of this review are uncertain about the effects of aPDT for halitosis control. Further RCTs with higher number of participants and long term assessments need to be conducted to support the use of this intervention. The protocol was registered in the PROSPERO database (number: CRD42020215319) on 19 November 2020—retrospectively registered.